Edaphic Characteristics of Rafflesia Habitats in Indonesia: Implications for Conservation and Propagation - Siahaan, Febrina artauli; Iryadi, Rajif; Lestari, Dewi (Universitas Gadjah Mada, 2024)
Rafflesia, a holoparasitic and endophytic plant, depends on its host, Tetrastigma spp., for survival, thus highlighting the critical interdependence between these species. Given the endangered status of Rafflesia due to anthropogenic pressures and narrow distribution, comprehensive conservation efforts are crucial. Ecological data on edaphic conditions, particularly the presence of the host, are important for effective conservation strategies. This study assessed soil properties across Rafflesia habitats on Sumatera, Borneo, and Java islands, revealing similarities in pH, carbon, nitrogen, cation exchange capacity (CEC), while the soil texture varied. These findings contribute valuable insights for informed conservation initiatives, both in-situ and ex-situ.